Low expression of activation marker cd69 and chemokine receptors ccr5 and cxcr3 on memory t cells after 2009 h1n1 influenza a antigen stimulation in vitro following h1n1 vaccination of hiv-infected individuals - Kriangkrai Chawansuntati (2018)
© 2015 Taylor & Francis Group, LLC. Unlike well-studied antibody responses to pandemic 2009 H1N1 influenza A virus vaccines in human immunodeficiency virus-infected (HIV+) individuals, less well understood are cell-mediated immune (CMI) responses to this antigen in this susceptible population. We investigated such influenza-specific CMI responses in 61 HIV+ individuals and in 20 HIV-negative (HIV-) healthy controls. Each was vaccinated with a single licensed dose of inactivated, split-virion vaccine comprised of the influenza A/California/7/2009 (H1N1) virus-like strain. Cells collected just prior to vaccination and at 1 and 3 months afterwards were stimulated in vitro with dialyzed vaccine antigen and assayed by flow cytometry for cytokines TNF-a, IFN-g, IL-2, and IL-10, for degranulation marker CD107a, as well as phenotypes of memory T-cell subpopulations. Comparable increases of cytokine-producing and CD107a-expressing T cells were observed in both HIV+ subjects and healthy HIV-controls. However, by 3 months post-vaccination, in vitro antigen stimulation of peripheral blood mononuclear cells induced greater expansion in controls of both CD4 and CD8 central memory and effector memory T cells, as well as higher expression of the activation marker CD69 and chemokine receptors CCR5 and CXCR3 than in HIV+ subjects. We concluded CD4+ and CD8+ memory T cells produce cytokines at comparable levels in both groups, whereas the expression after in vitro stimulation of molecules critical for cell migration to infection sites are lower in the HIV+ than in comparable controls. Further immunization strategies against influenza are needed to improve the CMI responses in people living with HIV.